DAMPAK PENGHAPUSAN KEBIJAKAN PROGRAM SEKOLAH GRATIS TERHADAP PRESTASI BELAJAR SISWA - Utami Luyani; Abu Mansyur; Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
The purpose of this research is to find out what are the impacts of the elimination of the free school program policy and the efforts made in implementing the policy of eliminating the free school program at SMP Negeri 1 Banyuasin II. The method used in this research is descriptive qualitative method. The data sources used consisted of research informants, archives and documents. The sampling technique used is snow ball sampling, where the sample taken is not emphasized on the number of samples but emphasized on the sample's understanding of the problem under study. The data collection technique used is interactive analysis technique.Based on the results of data analysis and discussion, it can be concluded that: the implementation of the elimination of the free school program at SMP Negeri 1 Banyuasin II has gone well. However, some of the impacts of the abolition of the free school program policy at SMP Negeri 1 Banyuasin II are that there are still school residents, especially students and parents, who have not fully accepted the policy. Because after the abolition of the free school program policy at SMP Negeri 1 Banyuasin II, especially parents of students from underprivileged groups became anxious to pay for their children's educational facilities. Not only that, some students who are currently performing well at school have declined due to the reduction in school facilities which has reduced students' enthusiasm for learning. Constraints that must be resolved and resolved immediately so that the implementation of the policy to eliminate the free school program can run optimally.